Framework for the Integration of Mobile Device Features in PLM - Hopf, Jens Michael (Reihe Informationsmanagement im Engineering Karlsruhe / Hrsg.: Karlsruher Institut für Technologie, Institut für Informationsmanagement im Ingenieurwesen (IMI), 2016)
Currently, companies have covered their business processes with stationary workstations while mobile business applications have limited relevance. Companies can cover their overall business processes more time-efficiently and cost-effectively when they integrate mobile users in workflows using mobile device features. The objective is a framework that can be used to model and control business applications for PLM processes using mobile device features to allow a totally new user experience.